Enduring liquid repellency through slippery ionic liquid-infused organogels - Salbaum, Tobias; Galvan, Yaraset; Haumann, Marco; Wasserscheid, Peter; Zarraga, Ramon; Vogel, Nicolas (Journal of Materials Chemistry A, 2021)
Lubricant-infused repellent coatings provide efficient repellency against contamination as the lubricant avoids direct contact between the surface and any contaminant to be repelled. Here, we address two mechanisms that potentially cause failure of the coating by loss of the liquid lubricant, and present a strategy for long-lasting coatings. We use ionic liquids as lubricants with extremely low vapor pressure. These are confined to the underlying substrate by means of functionalized polymeric gel that matches the chemical structure of the ionic liquids and thereby maximizes their molecular interactions. We use pentafluorophenol-based active ester polymers to provide a versatile platform that allows a convenient post-synthetic functionalization of the polymer network. The matching functional groups to efficiently bind a desired ionic liquid can thus be introduced via their amine-functionalized analogues, which we demonstrate for imidazole- and phosphonium-based molecules. We copolymerize benzophenone methacrylate for surface attachment and gel formation in one step. At 85 °C the surface and repellency properties remained constant for several months, outperforming thick, swollen PDMS films as the gold standard of lubricant-infused coatings.
CRIS-Team Scopus Importer:2021-02-26